Features of construction and investment projects as objects of organizational management - Stelmakh, O.; Molodko, O.; Shtyl, A.; Shcherban, B. (Ways to Improve Construction Efficiency, 2022)
The features of construction and investment projects as objects of organizational management are characterized by their high complexity, multi-component nature, and interdependence of implementation stages. Such projects integrate the interests of various participants: investors, contractors, clients, governmental authorities, and local communities, which necessitates the establishment of a clear organizational management structure and a resource coordination system. Construction and investment projects encompass a wide range of functions – from design, procurement of materials and resources, logistics, and construction works to commissioning and financial control. Effective management of these projects requires not only monitoring timelines and budgets but also ensuring the quality of construction processes, minimizing risks, and adapting to changes in the external environment, including economic, social, and regulatory factors. A key aspect of management is the integration of modern information and digital technologies, such as Building Information Modeling (BIM), project management systems, and ERP platforms, which enhance transparency, accuracy, and decision-making efficiency. An essential component is the application of analytical methods for risk assessment and resource management effectiveness, which ensures timely response to deviations and process optimization. The competitiveness of companies in the construction sector directly depends on their ability to adapt to changing market conditions, integrate financial, technological, and human resources, and ensure the sustainable development of project initiatives. As a result of systematic analysis, it has been determined that the features of construction and investment projects require the development of comprehensive organizational and management mechanisms that take into account the multidisciplinary nature of projects, the necessity to integrate public and private interests, and the use of innovative management technologies. The conclusions presented may serve as a theoretical basis for further research in construction project management and as a practical guide for companies aiming to enhance management decision-making, minimize risks, and ensure timely execution of construction and investment projects.